PENGARUH KOMITMEN ORGANISASI, JOB INSECURITY DAN DISIPLIN KERJA TERHADAP TURNOVER INTENTION KARYAWAN OUTSOURCING PADA PT. TIGA JANGKAR UTAMA DEPOK - , Dewita Suryati Ningsih, Radisya Winari , Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of organizational commitment, job insecurity  and work discipline on the turnover intention of outsourcing employees at PT. Tiga Jangkar Utama. In this study, data collection was carried out by distributing questionnaires using the proportional stratified random sampling method. The population in this study were outsourced employees of  PT. Tiga Jangkar Utama with a sample of  99 employees. While the data analysis used is multiple linear regression analysis with SPSS 22 tools.Based on the results of the analysis, it was found that simultaneously organizational commitment, job insecurity  and work discipline had a significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. Job insecurity  has a positive and significant effect on turnover intention. And work discipline has a negative and significant effect on turnover intention. With a coefficient of determination of 0.634 which means organizational commitment, job insecurity  and work discipline have an influence of 63,4% on the Turnover intention of outsourcing employees, while the remaining 36.6% describes other independent variables not observed in this study. Keywords: Organizational commitment, job insecurity , work discipline and turnover intention